Evaluation of hypomagnesaemia in diabetic patients with nephropathy in a reference clinical laboratory: a comparative cross sectional study - Sumaiya Qamar; Muhammad Anwar; Zujaja Hina Haroon; Afshan Bibi; Muhammad Usman Munir; Sobia Irum Kirmani (Journal of the Pakistan Medical Association, 2023)
Serum Magnesium plays a significant role in different diabetic complications. This comparative cross sectional study was conducted to evaluate serum magnesium levels in patients with Type 2 Diabetes Mellitus (T2DM) with and without nephropathy. A total of 182 diabetic patients (91 with nephropathy and 91 without nephropathy) were included. Odds ratio were calculated and Mann Whitney U test was used to compare quantitative variables; p<0.05 was considered significant. The results showed that 64/91 (70.3%) patients with nephropathy had hypomagnesaemia as compared to 21/91 (23.07%) patients without nephropathy. The risk of hypomagnesaemia was higher in patients with nephropathy than without nephropathy (Odds ratio 2.7 vs 0.34). Median magnesium levels (1.73 mg/dl) were lower in patients with nephropathy as compared to patients without nephropathy (2.09 mg/dl), p <0.01. It is concluded that magnesium levels were significantly lower in patients with diabetic nephropathy as compared to without nephropathy.